ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA PADA PROYEK PEMBANGUNAN GEDUNG RUSUN POLRES KABUPATEN SERAM BAGIAN TIMUR - Parni Tomia; Selly Metekohy; Jeffrey Payung Langi (Jurusan Teknik Sipil, 2023)
This research was conducted to analyze the factors that affect labor productivity in the construction project of the Police flats building in the resort, East Seram Regency. In this study, there are four factors studied, namely management factors, technical factors, human factors and technical factors, which are related to labor productivity. Therefore, the workforce as one of the parties involved in construction projects in the field must be considered, especially the factors that affect labor productivity in the field, it is very important to know in order to increase productivity in construction projects. For this reason, it is very important to maintain labor productivity not to decline. The research was conducted by distributing questionnaires to 30 respondents. The method of data analysis starts from the validity test, reliability test, multiple linear regression analysis to determine the hypothesis test, namely the t test and f test. The data analysis technique used is SPSS software version 26. The results of the T test show that there are three independent variables that significantly influence the dependent variable (labor productivity), namely management variables with t count (2.801) > t table (2.05), technical factors with t count (2.385) > t table (2, 05), human factor with t count (3.705) > t table (2.05). Simultaneously the four independent variables affect the dependent variable where the value of F count (44.956) > F table (2.74). And the most dominant factor seen from the results of the highest beta coefficient value, namely the human factor with a beta value of (40.8%), has a dominant effect on labor productivity.